Features of ensuring the rights of drug addicts for rehabilitation in Ukraine and the European Union: comparative legal aspect - Oleкsandr Shevchuk; Viktor Shevchuk; Ihor Kompaniiets; Serhii Lukashevych; Olena Tkachova (Juridical Tribune, 2022)
This article explores the problems of legal regulation of the implementation of the "right of drug addicts for rehabilitation" in Ukraine‚ and the foreign experience of individual EU countries in this area. The methodology of this scientific work is based on the system of methods of general scientific and special-legal methods of cognition. This paper reveals the features of the implementation of the "right of drug addicts to rehabilitation", establishes the concept of "rehabilitation of drug addicts", as well as the term "right of drug addicts to rehabilitation", the legal status of individual subjects is studied. Who are involved in the implementation of rehabilitation services for drug addicts. It is proposed to divide legal acts that cover the implementation of the “right of drug addicts to rehabilitation” into two groups: (1) general and (2) special. It is emphasized that the legal framework that would cover an effective state system for the rehabilitation of drug addicts in Ukraine has not yet been created, and as a result, a large number of drug addicts do not have access to rehabilitation services‚ or do not receive them at all. Directions for optimizing the legislation of Ukraine on the rehabilitation of drug addicts are given, with an emphasis on the implementation in practice of effective programs for the rehabilitation of adolescents who are dependent on psychoactive substances, taking into account their age groups. It is proposed to adopt a special Law of Ukraine on the rehabilitation of drug addicts. It is concluded that the effective implementation of advanced methods for the rehabilitation of drug addicts in Ukraine, taking into account international standards, should be a priority part of state policy, and it is important to use the principle of a holistic approach to the legal regulation of such rehabilitation assistance.